Răspuns :
a+b=428
a-b=8 => a=8+b
Îl înlocuim pe a în prima relație
8+b+b=428
8+2b=428
2b=428-8
2b=420
b=420:2
b=210
a=8+b=8+210=218
a-b=8 => a=8+b
Îl înlocuim pe a în prima relație
8+b+b=428
8+2b=428
2b=428-8
2b=420
b=420:2
b=210
a=8+b=8+210=218
a + b = 428
a - b = 8 de aici avem a = 8 + b
inlocuim in suma termenul a
8 + b + b = 428
8 + 2b = 428
2b = 428 - 8
2b = 420
b = 420 : 2
b = 210
a = 8 + b = > 8 + 210 = 218
218 + 210 = 428
218 - 210 = 8
a - b = 8 de aici avem a = 8 + b
inlocuim in suma termenul a
8 + b + b = 428
8 + 2b = 428
2b = 428 - 8
2b = 420
b = 420 : 2
b = 210
a = 8 + b = > 8 + 210 = 218
218 + 210 = 428
218 - 210 = 8